Class photograph - Gordon, John C. (photographer):::Creator::::::::::::
School children pose for a class photograph outside an unidentified building. The students hold diplomas. The boys are in suits and the girls wear a sailor inspired ensemble. The numbers "09" are painted on the pavement in front of them.